Angolan War of Liberation: Colonial-Communist Clash, 1961-1974 - Venter, Al J. (Cold War, 1945-1991 Series, 2018)
Cover -- Book Title -- Copyright -- CONTENTS -- Glossary -- Introduction -- 1. Unfolding -- 2. What Went on in Portugal's African Wars -- 3. The Land War -- 4. The Enemy: Divergent Options -- Plate section -- 5. Journalists -- 6. The Air War -- 7. Portugal's Commandos -- 8. The War in the East -- 9. Cabinda: Tiny Enclave Across the Congo -- 10. Why the War Went the Way it Did -- Bibliography -- About the Author -- Back Cover